DIVINE VALUES REFLECTED IN JALALUDDIN RUMI’S MASNAVI: A LINGUISTIC-PHILOSOPHICAL INQUIRY - Tuflih, Muhammad Alfian (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This study explores the manifestation of divine values in Jalaluddin Rumi’s Masnavi through the lens of the philosophy of language. As a monumental work of Sufi literature, the Masnavi employs symbolic, metaphoric, and dialogic forms of expression that reveal the mystical relationship between language and the experience of the Divine. Using a qualitative interpretive approach, this research analyzes selected verses to uncover how linguistic structures, especially metaphors and narrative parables, function as mediums for conveying spiritual truths. The findings show that Rumi’s language does not merely describe divinity but performs a transformative function—inviting readers to transcend literal meanings and engage in inner reflection (ta’ammul) and spiritual realization (ma’rifa). Divine values such as love, unity, compassion, and surrender are linguistically articulated in multilayered expressions, highlighting the inseparability of form and meaning in mystical discourse. This study affirms that, within Rumi’s Masnavi, language serves as both a philosophical and spiritual bridge that guides readers toward a deeper understanding of divine reality.